Cultural heritage of Islamic civilization - Alim, Abdul (Delhi : Random, 2012)
Exclusively based on "Indo-Islamic" period in India with special reference to Islamic art and architecture from various angles.
Includes index.
Keywords: Islamic civilization; Islamic art; Architecture, Mogul; Islamic architecture; Cultural property -- India; Cultural property